KAJIAN ALTERNATIF PEMBANGUNAN JEMBATAN PENAJAM- BALIKPAPAN - Irna Hendriyani (Jurnal Teknologi Berkelanjutan, 2013)
Land transportati on between East Kalimantan and South Kalimantan (Trans of South Kalimantan) is currently separated by Balikpapan baya swideas 1.8 to 3.7 km. This bay separetesthe North Penajam Paser Districtand Balikpapan City, East Kalimantan Province. Thus,crossing facilities are needed to connect the two areas. The facilitiesat this momentare ferries. Based on Technical Design Report Balang Island Bridge (2007), that the crossing facilitiesat this time will not beable to provide services in the future. There for the East Kalimantan Provincial Government made apolicy by building bridgeasone of the infra structure in the Trans of Kalimantan. The Penajam-Balikpapan bridgecon struction on the Balang Island made the trip longer than the ferry. This location were selected based on Pre-Feasibility Penajam- Balikpapan Bridge (1997) from other locations, namely Tanjung Batu-Kampung Baruand Nipah-nipah- Melawai. Based on the three locations, the bridgecon struction site locations were selected based on ranking of Multi Criteria Analysis (MCA) method. MCA is adecision making to oldeveloped for decision making process, using several criteria and select the best alternative based on those criteria. This methodus esperception of stakeholders on variables which are compared in the decision making process. This analysis involves 20 respondents from various sparties, based on criteria of ease of achieving goals, environmental spects, regional evelopment, the development of the road network system, social aspects and the benefit to costanalysis. As theresult, the second location, Tanjung Batu-Kampung Baru getthe first rank, and the third location, Nipah-nipah-Melawai get the second rank and the first location, Balang Island was the thir dranking. Benefit to Cost Ratio (BCR) value of location 2 is 1.33 and the net present value (NPV) is positive (+). This means that the location of Tanjung Batu-Kampung Baru is suitable asabridge construction sitefor Penajam-Balikpapan bridge.